(untitled) (Indian Journal of Geo-Marine Sciences (IJMS), 2026)
The current study used GIS mapping to identify potential fishing areas for Chrysochir aurea (Richardson, 1846), a commercially important sciaenid species, along the coast of West Bengal, India, by analysing its spatio-temporal distribution and abundance. Data were collected from two purposively selected trawlers operating along the coast of West Bengal from October 2021 to September 2022. Chrysochir aurea was found to be distributed at depths ranging from 10 m to 67 m, with the largest catch per hour value (19.07 kg h-1) occurring at depths ranging between 10 m and 30 m. The maximum catch was recorded in the southeast, which is regarded as a potential fishing zone along the coast. The predictive maps inferred that the species is more prevalent in the southeast region during pre-monsoon and both southeast and southwest regions during post-monsoon and winter seasons. Spatio-temporal distribution of C. aurea, recorded in the present study, will not only help in identifying the potential fishing grounds but also in framing management strategies for sustainable fisheries along the West Bengal coast.